FACTORS AFFECTING POLICY IMPLEMENTATION OF PAYMENT FOR FOREST ENVIRONMENT SERVICES IN HOA BINH PROVINCE - Quyen, Mai; Phuong Le, Nguyen; Thi Hai Ninh, Nguyen; Thi Minh Ngoc, Vu (Journal of Forestry Science and Technology, 2020)
The article is about implementation results of Payment for Forest Environment Service (PFES) policy and factors affecting policy implementation in Hoa Binh province. Implementation results are analyzed in terms of: services and supply boundaries of PFES; PFES payers and beneficiaries; Results of propaganda, inspection and supervision activities, results of forest areas receiving PFES money, results of collection and payment of PFES money. The paper analyzes the impact of 6 factors on the policy implementation process, including: PFES policy content; organizational structure; capacity of policy enforcement staff; resources; propaganda methods and beneficiary’s characteristics. Furthermore, by using a binary logistic model to analyze how the characteristics of the household affecting enforcement, the paper finds that number of forestry workers, years of experience in forestry production, the forest area to be paid under PFES policy, implementation location, the qualifications of the household head and the household’s ethnic composition have a significant impact on the policy enforcement of the households. Based on the results achieved, the research has proposed a number of solutions to improve the effectiveness of policy implementation in Hoa Binh province: Issue documents specifying policies; Policy dissemination and propaganda; Expand revenue sources with forest environment services users of ecotourism and aquaculture; Improve qualifications for the staff of the Provincial Forest Protection and Development Fund; Solutions for forest protection and development.